Socialna država in revščina - Korpič-Horvat, Etelka; Leskošek , Vesna; Senčur Peček , Darja; Antončič , Vojko Anton; Orešek , Natalija (2022)
Social State and Poverty. The Constitution of the Republic of Slovenia contains a provision specifying that Slovenia is a legal and social state. The initiative for issuing this monograph arose from the recognition that in Slovenia, the sensitivity for insufficient compliance with the social state principles is significantly lower than the sensitivity for an infringement of the principles of the rule of law. Low sensitivity for the non-respect of the principles of the rule of law is illustrated, inter alia, by tolerating poverty and social exclusion, or according to one of the authors in the monograph, it is reflected in considering poverty as bad luck of the individual. It also manifests itself in constitutional matters. Authors of the articles in the monograph point out that poverty is a multifaceted and complex social problem. Regardless of the differences between countries and societies, poverty always affects the dignity of a person. Authors of individual articles provide an analysis of the situation and propose possible solutions to various problems resulting from poverty and social exclusion. It is about finding a systemic solution to reduce poverty in Slovenia. To conclude, discussing legal aspects of the social state, systemic thematization of poverty, reducing poverty as a challenge for social policy and promoting awareness of poverty in Slovenia, are topics addressed by the authors in this monograph which represent the theoretical and empirical basis for enforcing social state principles and constitutional social rights.
Keywords: poverty; social exclusion; wellbeing; social state; Constitution; dignity